Strategies to increase soybean production by increasing the distribution of new superior varieties. Issue 1 (November 2021) - Yofa, R D; Perdana, R P; Aldillah, R; Muslim, C; Sunarsih,; Agustian, A
Abstract: Soybean production in Indonesia shows a downward trend over time, causing an increase in dependence on imports because the demand for soybeans is much greater. Therefore, efforts are needed to increase production by increasing productivity by using new soybean varieties, which are still very limited in distribution. This paper aims to identify the distribution of new soybean varieties, analyze the problems and factors affecting the distribution of new soybean varieties, and formulate strategies to increase the distribution of new soybean varieties. The study was conducted in the West Java and Central Java Provinces. The analysis method used in the study was qualitative descriptive. The analysis results show that in 2015-2019, soybean production in Indonesia, including in West Java and Central Java, shows a downward trend. Of the total distribution area of soybean varieties, the dominant varieties cultivated are Anjasmoro (61.48%), Wilis (10.66%), Grobogan (9.81%), Argomulyo (6.65%), and Baluran (4.01%). Meanwhile, the distribution of new soybean varieties is still very low, including Dena 1 variety (4.01%) and other new soybean varieties with a distribution area of less than 0.1% of the total distribution area. To increase the distribution of new soybean varieties, one of them can be done by developing seed breeders at the farmer level. Thus, the availability of the seeds of new soybean varieties can increase and farmers will find it easier to obtain these seeds.